Analisa Pengaruh Manajemen Rantai Pasok dalam Meningkatkan Kinerja Perusahaan UNIQLO dengan Menggunakan Sistem Enterprise Resource Planning (ERP) - Rizni Aulia Qadri; Fendy Cuandra; Shinta Dewi; Angeline Aurellia; Jeslin; Kristina; Sherry (Jurnal Cakrawala Ilmiah, 2022)
The supply chain is an essential element in a company. UNIQLO as a global clothing company implements ERP-based supply chains. This study aims to analyze the effect of supply chain management in improving UNIQLO performance by using an ERP system. The research method uses qualitative research with data collection techniques in the form of library research. Secondary data are used, namely articles, books, UNIQLO company website, and news. The results showed that UNIQLO supply chain management can affect the financial performance of the company. This is because the more responsive and efficient the supply chain, the better the company's performance is because it can support competitive strategies and vice versa. The competitive strategy determines the UNIQLO company's competitive ability with other companies so having a good competitive strategy will certainly bring greater profits for the company concerned.